Effects of Antithrombotic Drugs in a Rat Model of Aspirin-Insensitive Arterial Thrombosis - Schumacher, W A; Steinbacher, T E; Heran, C L; Megill, J R; Durham, S K (Thrombosis and Haemostasis, 1993)
These studies describe experimental conditions where aspirin is less effective than other antiplatelet and anticoagulant drugs in inhibiting acute arterial thrombosis. External electrolytic injury of the rat carotid artery was used to induce occlusive thrombi in 97% of vehicle-treated rats. Thrombi were revealed by light and electron microscopy to be comprised primarily of platelets enmeshed in a fibrin network. The thrombin inhibitor D-phenylalanyl-L-prolyl-L-arginyl chloromethy ketone (PPACK; 6 mg/kg, i. v.) decreased thrombus weight by 90%. Aspirin alone (1, 10 and 30 mg/kg, i. v.), dipyridamole alone (5 mg/kg i. v.) and aspirin (1 and 10 mg/kg, i. v.) in combination with dipyridamole (5 mg/kg, i. v.) did not inhibit thrombosis. The platelet-activating factor (PAF) antagonist, WEB 2086, (1 mg/kg i. v.) was also ineffective. Other drugs had intermediate activity. Thrombi were decreased 56% by the thromboxane receptor antagonist, BMS 180,291, either alone (5.8 mg/kg i.v.) or in combination with aspirin (10 mg/kg, i.v.). Heparin (900 U/kg, i.v.), warfarin (0.25 mg/kg, p.o. once daily for 3 days) and ticlopidine (200 mg/ kg, p.o. once daily for 3 days) reduced thrombus weight by 63, 73 and 43% respectively. Reductions in thrombus weight were always associated with improvements in either average blood flow or vessel patency.